2022
DOI: 10.3390/cells11050829
|View full text |Cite
|
Sign up to set email alerts
|

Hsp70 in Redox Homeostasis

Abstract: Cellular redox homeostasis is precisely balanced by generation and elimination of reactive oxygen species (ROS). ROS are not only capable of causing oxidation of proteins, lipids and DNA to damage cells but can also act as signaling molecules to modulate transcription factors and epigenetic pathways that determine cell survival and death. Hsp70 proteins are central hubs for proteostasis and are important factors to ameliorate damage from different kinds of stress including oxidative stress. Hsp70 members often… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 163 publications
(217 reference statements)
2
36
0
Order By: Relevance
“…In addition, the adaptive responses of broilers to pre-slaughter transport stress were insufficient, as the activities of antioxidant enzymes, including T-AOC, T-SOD, and GSH-Px, remained unchanged, which is in accordance with the findings obtained by Liao et al [ 40 ]. HSP70 exerts its cytoprotective effect by facilitating the degradation of damaged oxidized proteins via the ubiquitin-proteasome system, as well as by inducing the expression of key antioxidant enzymes and adjusting their activities under oxidative stress [ 41 ]. According to Gu et al [ 14 ], HSP70 significantly elevated antioxidant enzyme activities and inhibited lipid peroxidation to protect the intestinal mucosa of broilers from heat-stress injury.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the adaptive responses of broilers to pre-slaughter transport stress were insufficient, as the activities of antioxidant enzymes, including T-AOC, T-SOD, and GSH-Px, remained unchanged, which is in accordance with the findings obtained by Liao et al [ 40 ]. HSP70 exerts its cytoprotective effect by facilitating the degradation of damaged oxidized proteins via the ubiquitin-proteasome system, as well as by inducing the expression of key antioxidant enzymes and adjusting their activities under oxidative stress [ 41 ]. According to Gu et al [ 14 ], HSP70 significantly elevated antioxidant enzyme activities and inhibited lipid peroxidation to protect the intestinal mucosa of broilers from heat-stress injury.…”
Section: Discussionmentioning
confidence: 99%
“…Protein structural maintenance and stability is an outcome of the intermolecular and intramolecular interactions. Anything potentially disturbing these interactions, such as temperature, oxidative stress, and heavy metals, is a proteotoxic stressor and leads to protein misfolding and potentially aggregation [ 20 , 40 , 41 , 42 ]. We confirmed the presence of proteotoxic stress by measuring proteome aggregation and cell proliferation, and validated the dose-response nature of stress by monitoring the Hsp70 gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…We analyzed the proteasome components 19S and 20S. The lack of changes in protein levels of the regulatory cap component 19S proteasome and in the proteolytic signaling hub HSP70 [ 64 ] suggests that the effects were at the level of the catalytic 20S proteasome or immunoproteasome. We found an increase in trypsin-like enzymatic activity in the cerebral cortex, whereas other authors have reported also increases in chymotrypsin-like and caspase-like enzymatic activities in the hippocampus of mice submitted to voluntary wheel running [ 65 ].…”
Section: Discussionmentioning
confidence: 99%